International consensus on EEG reactivity testing after cardiac arrest: Towards standardization. (October 2018) - Admiraal, M.M.; van Rootselaar, A.F.; Horn, J.
Abstract: Background: In patients after cardiac arrest (CA), EEG reactivity (EEG-R) is proposed as a prognostic marker. However, no clear guidelines exist on how to test EEG-R and definitions are unspecific. Therefore, we aimed at forming international consensus regarding a stimulus protocol for EEG-R testing and the interpretation of EEG-R in daily clinical care. Methods: We invited 30 international experts on EEG in patients after CA for participation in a two round Delphi study. Consensus was defined as ≥75% agreement, 66–75% agreement was included as recommendation. Results: In the first round 24 experts participated (80% response rate) of whom 22 finished the second round (8% drop-out). Consensus was reached on several parts of the stimulus protocol: Clapping, calling out the patient's name and nail bed pressure should be executed and each stimulus at least three times with recommended duration of at least 5 s. The patient should not be stimulated before EEG-R testing and information on sedation/analgesics should be provided. The consensus definition of EEG-R is "A reproducible change in the EEG in response to stimulation" and appearance of muscle-, movement- and eye blink artefacts, spinal movements and electrographic seizure induction do not qualify as reactive. Almost all respondents agreed that this consensus protocol should also be used in comatose patients with other etiologies. Conclusion: This international consensus statement on EEG-R in patients after CA can be regarded as starting point. At the moment evidence is limited and our study can provide best-practice guidance in patients after CA as well as other comatose patients.